Development and Characterization of Semi-IPN Silver Nanocomposite Hydrogels for Antibacterial Applications. (21st March 2013) - Chandra Babu, A.; Prabhakar, M. N.; Suresh Babu, A.; Mallikarjuna, B.; Subha, M. C. S.; Chowdoji Rao, K.
Abstract : Sodium carboxymethyl cellulose/poly(acrylamide-co-2-acrylamido-2-methylpropane sulfonic acid) semi-interpenetrating polymer network (semi-IPN) hydrogels were prepared by using free radical polymerization technique. Silver nanoparticles were formed by reduction of silver nitrate in semi-IPN hydrogels with sodium borohydrate at room temperature. UV-visible spectroscopy, thermogravimetrical analysis, X-ray diffractometry, scanning electron microscopy, and transmission electron microscopy techniques were used to characterize the formation of silver nanoparticles in hydrogels. SEM images indicated clearly the formation of group of silver nanoparticles with size range of 10–20 nm. The sizes of silver nanoparticles were also supported by transmission electron microscopy results. The semi-IPN silver nanocomposite hydrogels reported here might be a potentially smart material in the range of applications of antibacterial activity.